Are You Sure: Preference and Ambivalence in Delay Discounting - Grunevski, Sergej; Smith, Aaron P.; Yi, Richard (Frontiers in Behavioral Neuroscience, 2022)
Delay discounting research has become ubiquitous due to its robust associations with clinical outcomes. Typical delay discounting tasks involve multiple trials in which participants indicate preference between smaller, sooner and larger, later rewards. Scoring of these binary choice tasks has not considered trial-level ambivalence as a possible decision-making construct. The present study explored the extent to which trial-level ambivalence varied within-individual using an established assessment of delay discounting (the Monetary Choice Questionnaire). Results indicate that degree of ambivalence peaks around the trials associated with the delay discounting rate. Moreover, ambivalence is associated with a diminished impact of reward delay differences on choice, where greater delay differences decrease the odds of choosing the larger, later rewards. Taken together, we believe ambivalence to be a relevant construct for research on intertemporal decision making, and it may be particularly useful in the study of manipulations on individual rates of delay discounting.